Formação de leitores de literatura no Pibid: análise semiótica de relatos de experiências dos bolsistas da licenciatura de letras da UFT. - Santos, Aline Silva dos (Universidade Federal do Tocantins, 2023)
In this paper, we approach actions related to the education of readers in the Subproject PIBID/Letras part of Letras course at Araguaína, Universidade Federal do Tocantins – UFT. The study object is 12 surveys prepared by the scholarship students among other students, which covers a three month study, from April to June of 2016. Based on the discursive semiotic theory, that investigates the meaning, prioritizing some of its categories, but most specifically, those who are known as syntax level of narrative. At this level are comprehended the interactional dynamic between subjects and subjects and objects, visualizing the strategies of seduction through manipulation predicted in the interaction between teachers and students in the teaching-learning process. It is also taken in consideration a survey answered by the Subproject’s coordinator in the field of the study in this institution. As for the structure of this paper, initially it is specified how the program works, then it is reported the issue of the education of readers. At the end, the reports are analyzed from the semiotic perspective. Parting from the importance of the Subproject to literature education, the research proposed to answer the question: What are the contributions of the Subproject PIBID/Letras Araguaína to the education of readers? Considering the efforts of literary projects and the problems faced, especially the rejection of the students towards the canonic literature proposed by the government in the curriculum of Tocantins high schools.